Interpreting Gene Expression Effects of Disease-Associated Variants: A Lesson from SNCA rs356168 - Glenn, Omolara-Chinue; Tagliafierro, Lidia; Beach, Thomas G.; Woltjer, Randy L.; Chiba-Falek, Ornit (Frontiers in Genetics, 2017)
The SNCA intronic single nucleotide polymorphism (SNP), rs356168, has been associated with Parkinson’s disease (PD) in large genome wide association studies (GWAS). Recently, the PD-risk allele, rs356168-G was shown to increase SNCA-mRNA expression using genome edited human induced pluripotent stem cells (iPSC)-derived neurons. In this study, as means of validation, we tested the effect of rs356168 on total SNCA-mRNA levels using brain tissues, temporal and frontal cortex, from healthy control donors. Carriers of the rs356168-G allele demonstrated a borderline significant decrease of SNCA-mRNA levels in temporal brain tissues (p=0.02) compared to individuals homozygous for the ‘A’ allele. Similar trend, but weak, was observed in the analysis of frontal cortex samples, however, this analysis did not reach statistical significance. These results conflict with the recently reported effect of SNCA SNP rs356168 described above. Our study conveys the need to carefully interpret the precise molecular mechanism by which rs356168, or another tightly linked variant, affects the regulation of SNCA expression. The regulatory mechanisms that contribute to the observed associations between PD and the SNCA-3’ linkage disequilibrium (LD) region warrant further investigations.